2014
DOI: 10.1158/1055-9965.epi-14-0386
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Transmission of Oral Human Papillomavirus Infection among Men

Abstract: We estimated the prevalence of oral human papillomavirus (HPV) and assessed risk factors among young heterosexual men participating in the HPV Infection and Transmission among Couples through Heterosexual Activity (HITCH) study. Oral and genital HPV samples were collected from 222 men and their female partners who were participating in the HITCH study, a longitudinal cohort on HPV transmission among heterosexual couples. Demographic and behavioral data were collected through self-administered computer question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 14 publications
5
39
0
Order By: Relevance
“…In addition, that association was significant in females (OR: 2.19, 95% CI: 1.26 - 3.82, P = 0.0058) [12, 13, 23], indicating a strong relationship between females and HPV prevalence. In their previous study, Dahlstrom et al found a statistically significant association between smoking and oral HPV infection in males [13]. Together, these results suggest that oral sex experience and smoking are related to oral HPV infection, while it is important to note that smoking is strongly associated with oral HPV infection in females.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, that association was significant in females (OR: 2.19, 95% CI: 1.26 - 3.82, P = 0.0058) [12, 13, 23], indicating a strong relationship between females and HPV prevalence. In their previous study, Dahlstrom et al found a statistically significant association between smoking and oral HPV infection in males [13]. Together, these results suggest that oral sex experience and smoking are related to oral HPV infection, while it is important to note that smoking is strongly associated with oral HPV infection in females.…”
Section: Resultsmentioning
confidence: 99%
“…In Japan, the decreasing average age at starting sexual activities may have increased the HPV infection rate in young people [48, 49]. The most common high-risk type of HPV infection seen in the oral cavity and cervix of sexually active young people is HPV16 [9, 12, 13, 27, 47]. Furthermore, HPV42 is a common low-risk HPV type seen in those locations in young females [9, 27], while HPV18 is commonly found in the cervix but not the oral cavity in young subjects [9, 12, 13, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the virus can be transferred through oral sex to a person who has genital HPV infection, while others claim the infection can spread by kissing with a person with oral HPV infection and lately there are more bold claims to carry of the virus in simple contact (16).…”
Section: S S U E 2 2 0 1mentioning
confidence: 99%
“…3,4 Transmission of the virus, which occurs through orogenital contact or oral-oral contact, and other sexual behavior [5][6][7] may explain the presence of HPV in the oral cavity and its possible relation with HNC.…”
mentioning
confidence: 99%